2010
DOI: 10.1126/science.1191803
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Tolerance in Plants Requires Lipid Remodeling at the Outer Chloroplast Membrane

Abstract: Plants show complex adaptations to freezing that prevent cell damage caused by cellular dehydration. Lipid remodeling of cell membranes during dehydration is one critical mechanism countering loss of membrane integrity and cell death. SENSITIVE TO FREEZING 2 (SFR2), a gene essential for freezing tolerance in Arabidopsis, encodes a galactolipid remodeling enzyme of the outer chloroplast envelope membrane. SFR2 processively transfers galactosyl residues from the abundant monogalactolipid to different galactolipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
383
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(400 citation statements)
references
References 28 publications
17
383
0
Order By: Relevance
“…Accumulation of TAGs in leaves has been reported in Arabidopsis under freezing temperature and involves SENSITIVE TO FREEZING2 (SFR2), which encodes a galactolipid remodeling enzyme contributing to TAG accumulation (Moellering et al, 2010). We did not detect a change in SFR2 transcript level in wheat (Supplemental Data Set 9).…”
Section: Rna-seq Analysis Of Wheat Transcriptomementioning
confidence: 62%
See 1 more Smart Citation
“…Accumulation of TAGs in leaves has been reported in Arabidopsis under freezing temperature and involves SENSITIVE TO FREEZING2 (SFR2), which encodes a galactolipid remodeling enzyme contributing to TAG accumulation (Moellering et al, 2010). We did not detect a change in SFR2 transcript level in wheat (Supplemental Data Set 9).…”
Section: Rna-seq Analysis Of Wheat Transcriptomementioning
confidence: 62%
“…We did not detect a change in SFR2 transcript level in wheat (Supplemental Data Set 9). However, studies have shown that SFR2 activity is primarily regulated at the posttranslational level during freezing tolerance (Moellering et al, 2010). Five genes potentially involved in TAG breakdown including LIPASE1 (El-Kouhen et al, 2005), SUGAR-DEPENDENT1 (Eastmond, 2006), MPL1 (El- Kouhen et al, 2005), and two putative TAGLs were downregulated more than 2-fold.…”
Section: Rna-seq Analysis Of Wheat Transcriptomementioning
confidence: 99%
“…Interestingly, AZI1 is induced in roots after ISR-inducing bacteria colonization 54 . A common feature of different stress signalling pathways may be the remodelling of chloroplast OEM lipids as well as PM lipids and reactive oxygen species production 55,56 . Moreover, several HyPRPs from different plant species have been reported to have roles in abiotic stress tolerance 38,[57][58][59] .…”
Section: Resultsmentioning
confidence: 99%
“…One such candidate protein is SENSITIVE TO FREEZING2 (SFR2). SFR2 converts MGDG to DGDG and oligogalactolipids by transglycosylation with a concomitant production of DAG, which can be further metabolized to TAG (Moellering et al, 2010). The tgd1-1 mutant accumulates oligogalactolipids in leaves, indicating that SFR2 is activated in this mutant (Xu et al, 2003(Xu et al, , 2008Awai et al, 2006).…”
Section: Disruption Of Sensitive To Freezing2 Affects Lipid Content Amentioning
confidence: 99%